Effect of Retained Austenite on the Micro-structure and Mechanical Properties of AI-SI4340 High Strength Low Alloy Steel (HSLA steel) Using Magnetic Saturation Measurement and X-Ray Diffraction methods - Abdulkareem, Nagham. M; Jabbar, Murtadha A. (Basrah Journal for Engineering Sciences, 2017)
Retained Austenite (RA) has great deal with the me- chanical properties of high strength low alloy steel. Therefore, in this paper, Retained Austenite volume fractions have been evaluated in AISI4340 alloy steel using two well-known meth- ods, X-Ray diffraction (XRD) and magnetic measurement methods. The specimens were heat treated using different heat- ing temperature and different cooling rate (different quenching media). A comparison between the results of two methods proved that there results were approximately Identical .The results show that Retained Austenite formation increase as heating (Austenizing ) temperature increase for the same quenching media ,as well as ,it increases by increasing cooling rate . The maximum amount of Retained Austenite found as (27.2 Wt %) which recognized when the specimens heated up to 1000˚C then quenched in Water while the minimum amount of Retained Austenite found as ( 7.06 wt%) when the specimens heated up to ( 800 ˚C) then quenched in Sand. Hardness tests using Vickers and Rockwell methods were used and the results show that hardness values decreased with increasing heating temperatures and the maximum Vickers micro-hardness and Rockwell hardness numbers were equal to (121.8HRB) and ( 516.35 HV) which were detected when heating up of the speci- mens were up to 800 ˚C then quenched in water. Tensile tests show that increasing cooling rate lead to increasing in Strength due to increasing of hardness which in turn, leads to increase in yielding points and ultimate strengths. Retained austenite effects on microstructure were investigated using scanning electron microscopy (SEM) and optical microscopy and the results show that at low cooling rate the microstructure consist of bainite and/or martensite phase with small amount of re- tained austenite, while, increasing heating temperature and cooling rate results in microstructure consist of martensite and retained austenite phases.